A Case Report of a Late-Onset Systemic Lupus Erythematosus Like- Induced by Carbamazepine Therapy - Hussein, Farhad N. (Journal of the Faculty of Medicine Baghdad, 2011)
A case of systemic lupus erythematosus like induced by carbamazepine therapy in a 27 year old female patient with left sided trigeminal neuralgia had been recorded, 9 years from starting carbamazepine therapy. The patient condition improved clinically 3 days after withdrawal of carbamazepine , the titer of antinuclear antibodies dropped from 1/640 to 1/80 after 3 weeks, and disappear completely after 6 months follow up.